Foreign direct investment, prices and efficiency: Evidence from India - Nesma Ali; Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
This paper uses a rich panel data set of Indian manufacturing firms to analyze the effects of foreign direct investment (FDI) on various outcomes of domestic firms. We apply recent methodological advances in the estimation of production functions together with detailed product-level information on prices and quantities to estimate physical productivity, markups and marginal costs. Our results indicate the importance of price adjustments which stem from competitive pressure and a pass-through of cost savings to consumers. In line with the previous literature, we find little evidence for spillovers based on commonly used measures of revenue productivity. In contrast, we measure sizable efficiency gains using measures that are not affected by pricing heterogeneity, such as marginal costs and physical productivity. Exploiting exogenous variation from India's FDI liberalization, we provide evidence that the relationship between exposure to FDI and efficiency is causal. Our results suggest that knowledge spills over across product categories within industries and mainly benefits producers of high-quality products. We also provide evidence that FDI spillovers are stronger for joint ventures and when foreign investors enter via acquisitions.
Keywords: F61; F23; G34; L25; D22; D24; 330; Foreign Direct Investment; Spillovers; Productivity; Marginal Costs; Prices; Markups; Multi-Product Firms